Treatment-resistant papilledema in a boy with homocystinuria - Neven, Lisa; Casteels, Ingele; Witters, Peter; Jansen, Katrien; Cassiman, Catherine (Belgian Journal of Paediatrics, 2023)
We report an 8-year old boy with the diagnosis of pyridoxine non-responsive cystathione beta-synthase deficiency. At a routine ophthalmological examination bilateral papilledema was detected on fundoscopy. Urgent brain imaging showed the typical signs of elevated intracranial pressure and cerebral edema. Laboratory results revealed high plasma methionine levels, secondary to treatment with betaine and a catabolic state because of a low calorie intake. Methionine excess is usually reversible with discontinuation of betaine together with a methionine restricted diet. In our patient however, a ventriculoperitoneal shunt placement was required to lower intracranial pressure and resolve the bilateral papilledema.